Enzyme immunoassay for detection of antibodies against eastern equine encephalomyelitis virus in sentinel chickens. - Olson, J G (1991)
We developed an enzyme immunoassay (EIA) for the detection of immunoglobulin M (IgM) and IgG subclass antibodies directed against eastern equine encephalomyelitis (EEE) virus in chickens. The assays were compared with the serum plaque reduction neutralization test (PRNT) and the hemagglutination inhibition (HI) test for ability to detect antibodies against EEE virus in laboratory-infected birds. No cross-reactivity was detected in serum from chickens inoculated with St. Louis encephalitis or Highlands J virus. The interval after infection when EEE virus-specific antibodies were first detected by IgM and IgG EIAs was found to be similar to that determined by the PRNT and HI tests: 2 to 4 days. The IgG EIA, PRNT, and HI test detected antibodies to EEE virus for at least 27 to 30 days after inoculation. In contrast, serum from five of seven chickens did not contain detectable IgM 30 days after infection. Similarly, in all three naturally infected sentinel chickens from Maryland, IgM class antibody was undetectable 1 to 5 weeks after IgM was initially detected. EIAs provide simple and rapid alternatives to traditional tests for monitoring EEE virus infections in sentinel chicken flocks. Moreover, the IgM EIA provides a means to separate recently infected chickens from those infected greater than or equal to 1 month earlier.